Comparative analysis of hydraulic crane-manipulating installations transport and technological machines and industrial robots hydraulic manipulators - Lagerev I.A. (Научно-технический вестник Брянского государственного университета)
The article presents results of comparative analysis of hydraulic crane-manipulator installations of mobile transport and technological machines and hydraulic manipulators of industrial robots. The comparative analysis is based on consid-eration of a wide range of types and sizes indicated technical devices of both domestic and foreign production: 1580 structures of cranes and more than 450 structures of industrial robots. It was performed in the following areas: func-tional purpose and basic technical characteristics; a design; the loading conditions of the model and failures in operation process; approaches to the design, calculation methods and mathematical modeling. The conclusions about the degree of similarity and the degree of difference hydraulic crane-manipulator installations of transport and technological ma-chines and hydraulic industrial robot manipulators from the standpoint of their design and modeling occurring in them during operation of dynamic and structural processes.